Clinical spectrum of COVID-19 at a national referral hospital in western Kenya during the period 2020–2021 - Ogalo, Edith A.; Gudu, Edwin; Andale, Thomas; Korir, Daisy; Ndege, Samson; Simiyu, Tabu; Olekuyo, Richard; Mwangi, Henry; Kimaiyo, Sylvester; Aruasa, Wilson (Frontiers in Virology, 2023)
We describe the clinical spectrum of COVID-19 in Western Kenya during the period 6 th April 2020 to 31 st May 2021, providing baseline data for further studies into COVID-19 in Kenya.We did a retrospective chart review of laboratory and inpatient files of patients diagnosed and managed for COVID-19 at the Moi Teaching and Referral Hospital in Kenya and analyzed the data using STATA version 16 and calculated measures of association at 95% CI.The patients (N=1770) had a mean age of mean age of 43 years (SD 20) and 55.4% were male. Close to 70% had asymptomatic disease, with the symptomatic cases largely being respiratory in nature. One quarter had co-morbidities. The case fatality rate was 13.6% (n= 240).Male gender increased the odds of mortality by 1.69 (CI 1.27 -2.25, p=<0.001) while presence of co-morbidity increased the odds of mortality by 3.16 (CI 2.38 -4.18, p=<0.001). Those aged 59 years and above were 18 times more likely to die from COVID-19 compared to those below 15 years (CI 1.61-90.66, p=0.015).COVID-19 had a significantly high mortality rate in western Kenya. Male gender and presence of co-morbidity increase risk of severe disease and mortality.